Trimethyltin-Induced Microglial Activation via NADPH Oxidase and MAPKs Pathway in BV-2 Microglial Cells - Da Jung Kim; Yong Sik Kim (Mediators of Inflammation)
Trimethyltin (TMT) is known as a potent neurotoxicant that causes neuronal cell death and neuroinflammation, particularly in the hippocampus. Microglial activation is one of the prominent pathological features of TMT neurotoxicity. Nevertheless, it remains unclear how microglial activation occurs in TMT intoxication. In this study, we aimed to investigate the signaling pathways in TMT-induced microglial activation using BV-2 murine microglial cells. Our results revealed that TMT generates reactive oxygen species (ROS) and increases the expression of CD11b and nuclear factor-κB- (NF-κB-) mediated nitric oxide (NO) and tumor necrosis factor- (TNF-) α in BV-2 cells. We also observed that NF-κB activation was controlled by p38 and JNK phosphorylation. Moreover, TMT-induced ROS generation occurred via nicotinamide adenine dinucleotide phosphate (NADPH) oxidase in BV-2 cells. Interestingly, treatment with the NADPH oxidase inhibitor apocynin significantly suppressed p38 and JNK phosphorylation and NF-κB activation and ultimately the production of proinflammatory mediators upon TMT exposure. These findings indicate that NADPH oxidase-dependent ROS generation activated p38 and JNK mitogen-activated protein kinases (MAPKs), which then stimulated NF-κB to release proinflammatory mediators in the TMT-treated BV-2 cells.